Neoadjuvant adebrelimab combined with chemotherapy (cisplatin/carboplatin and etoposide) for limited-stage small-cell lung cancer: a study protocol of phase 2 trial (NIUS) - Yan Zhang; Qian Huang; Mengxia Li; Xi Zheng; Yanyang Liu; Long Tian; Guizhi Chen; Hongyu Xu; Daxing Zhu (BMJ Open)
Introduction Small-cell lung cancer (SCLC) is a highly malignant neuroendocrine tumour, and concurrent chemoradiotherapy is the current recommended treatment for limited-stage SCLC. However, the overall survival (OS) of patients with SCLC remains poor. Therefore, improving the survival of patients with SCLC and benefitting more patients are urgent clinical requirements. Immunotherapy has achieved good efficacy in extensive-stage SCLC and non-SCLC. However, the use of neoadjuvant immunotherapy in limited-stage SCLC is unknown but promising. To this end, we plan to conduct a study on adebrelimab in combination with chemotherapy for the neoadjuvant treatment of limited-stage SCLC.Methods and analysis This will be a single-arm, prospective study. The primary endpoint of this study will be a pathological complete remission rate. The secondary endpoints will be a major pathological response, objective response rate, event-free survival, OS, R0 resection rate, safety and potential predictive biomarker parameters related to efficacy in peripheral blood samples, including minimal residual disease, circulating tumour cells and cluster of differentiation (CD) 4/CD8. This study will enrol 28 patients.Ethics and dissemination This study was approved by the Biomedical Ethics Review Committee of West China Hospital, Sichuan University, on 1 August 2023 (grant number 2023[987]). The version of this study protocol is V7.0. The patients have been enrolled since September 2023. This study will conclude in January 2026, and the results will be presented to peer-reviewed medical journals and international scientific conferences in 2027. This study will provide important data on whether neoadjuvant treatment with adebrelimab combined with chemotherapy is clinically beneficial in patients with limited-stage SCLC.(Prospective study of neoadjuvant adebrelimab combined with chemotherapy in limited-stage SCLC; Chinese Clinical Trial Registry (ChiCTR), www.chictr.org.cn/; Number, ChiCTR2300074591.)Trial registration number ChiCTR2300074591